Efforts in Preventing and Curing HIV/AIDS: A Systematic Review - Exposto, Levi Anatolia S.M.; Seixas, Cleofas da Costa; Ximenes, Leonardo; Pires, Cesaltino Maria (Interdisciplinary Social Studies, 2021)
Background: HIV/AIDS disease is a disease that continues to grow and become a global problem that hit the world. HIV/AIDS is a public health problem that requires serious attention. AIDS is declared a deadly disease because it has a Case Fatality Rate (CFR) of 100% within 5 years means within 5 years after the patient is declared to have AIDS on average will die. Aim: Therefore, the purpose of writing systematic review is to know the effective prevention and treatment of HIV / AIDS for HIV. Method: The entire extracted article is taken from several sources namely Google Scholar, Pubmed, Emerald Insight, DOAJ. Furthermore, screening of titles, abstracts and selection of content or content according to inclusion and exclusion is obtained 10 articles that are further analyzed. Findings: Effective efforts to prevent yourself from HIV/AIDS infection are: Abstinance, befaithful, Condom, Drug and Education. Treatment of HIV/AIDS with the ARV method is considered effective in HIV/AIDS treatment. Antiretroviral therapy treats HIV infection with several medications. ARVs do not kill the virus but are able to slow the rate of growth of the virus, as well as HIV disease and improve health status, quality of life for HIV, decrease hospitalization due to HIV, reduce AIDS-related deaths, reduce mother to child transmission (MTCT) or what we know as mother-to-baby transmission and also provide new hope for people with HIV / AIDS to be able to live longer.